Benzoic acid-doped nickel / cobalt bimetallic MOF-based aqueous battery positive electrode material and preparation method and application thereof

By doping benzoic acid in nickel/cobalt bimetallic MOF and ligand doping by hydrothermal method, the problem of low capacity and low energy density of nickel-based MOF materials in aqueous mixed zinc batteries is solved, and a positive electrode material preparation with high capacity and excellent electrochemical performance is achieved, which improves the energy efficiency and service life of the battery.

CN119591892APending Publication Date: 2025-03-11ZHEJIANG UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411759559.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

When the existing nickel-based MOF materials are used as the positive electrode material in water-based mixed zinc batteries, they have low capacity, low energy density and poor cycle stability, resulting in little improvement in energy efficiency.

Method used

By doping benzoic acid in nickel/cobalt bimetallic MOF and ligand doping by one-step hydrothermal method, the process flow is simplified and the synthesis efficiency is improved, a positive electrode material with high capacity and excellent electrochemical properties is prepared.

Benefits of technology

The electrocatalytic activity and electrochemical properties of nickel-based MOF are improved, the redox reaction activity is enhanced, the electrode capacity and energy density are improved, and the rate performance and stability are shown.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591892A_ABST
    Figure CN119591892A_ABST
Patent Text Reader

Abstract

The invention provides a benzoic acid-doped nickel / cobalt bimetallic MOF-based aqueous battery positive electrode material and a preparation method and application thereof, and the preparation method comprises the following steps: dipping a porous carrier in a reaction solution for solvothermal reaction to prepare the benzoic acid-doped nickel / cobalt bimetallic MOF-based positive electrode material, the reaction liquid at least comprises Ni < 2 + >, Co < 2 + > and ligands, and the ligands comprise terephthalic acid and benzoic acid. According to the benzoic acid doped nickel / cobalt bimetal MOF-based aqueous battery positive electrode material prepared by the invention, the OER performance and the electrochemical performance of nickel-based MOF are improved, the OER overpotential is 284 mV, the OER overpotential can be stabilized for 22 hours under an alkaline condition, and the current retention rate is close to 100%. The capacity of the positive electrode material reaches 442.96 mAh g <-1 > under the current density of 1 mA cm <-2 > and is far higher than that of most of the existing NiCoMOF positive electrodes, the capacity can still be kept at 229.44 mAh g <-1 > under the high current density of 30 mA cm <-2 >, and the positive electrode material has good rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of material technology, and in particular to a benzoic acid-doped nickel / cobalt bimetallic MOF-based aqueous battery positive electrode material and a preparation method and application thereof. Background Art

[0002] As global energy demand continues to expand, it is imperative to develop energy storage devices with high energy efficiency to store renewable energy. Rechargeable zinc-air batteries have excellent theoretical capacity (820 mAh g -1 ), low cost and inherent safety (aqueous electrolyte), and are considered to be a viable alternative to lithium-ion batteries. Zinc-air batteries lack an effective bifunctional catalyst air electrode, which results in high overpotentials for both the oxygen evolution reaction (OER) and the oxygen reduction reaction (ORR), making their actual operating voltage lower than 1.4 V, resulting in a low round-trip energy efficiency of the battery (50-65%). Zn-based aqueous batteries have attracted a lot of attention due to their high safety, environmental friendliness and low cost. Among these aqueous rechargeable batteries, Ni-Zn batteries are considered to be a promising alternative to LIBs due to their high operating voltage (1.8 V) and safety. Currently, the main disadvantages of Ni-Zn batteries are poor cycling stability and low energy density. At the cell level, the Ni in Ni-Zn batteries is converted to 2+ By connecting the redox reaction in the Zn-Air battery with the ORR / OER in the Zn-Air battery, the charging platform of the hybrid battery can be significantly reduced, the discharge platform can be increased, the capacity can be increased, and the energy efficiency and service life can be improved.

[0003] In recent years, nickel-based materials have been designed due to their low cost and good OER activity. Various nanostructured materials such as NiO, Cu X O@NiFe-LDH,Ni3S2,Co 1.29 Ni 1.71 However, these materials have a large difference in oxygen reduction potential between OER and ORR as positive electrodes for aqueous hybrid zinc batteries, and the electrode capacity does not exceed 300 mAh g -1 , which makes the metal-Zn battery account for a small proportion in the cycle process of the hybrid device, resulting in little improvement in the energy efficiency of the hybrid device.

[0004] Metal-organic frameworks (MOFs) are multidimensional periodic porous skeleton materials, mainly composed of transition metal ions and organic ligands coordinated by complexation. However, most MOFs have poor conductivity and stability. By doping MOFs with different metal ions, an adjustable band structure can be generated in MOFs. This method can adjust the energy levels of the valence band and conduction band to promote charge transfer.

[0005] Organic ligands, as bridges between metal ions in MOFs, play an important role in adjusting the topology and chemical coordination of compounds in MOFs. In recent years, ligand deletion and exchange have introduced unsaturated coordination, lattice strain and defects into MOFs, which is considered to be an effective strategy to adjust the microstructure and physicochemical properties of MOFs, resulting in the exposure of more active sites and optimized conductivity. In the synthesis of nickel-based MOFs, terephthalic acid (PTA) is the most commonly used organic ligand, which has a symmetrical carboxylic acid structure and uses a dicarboxyl linker to coordinate with metal ions. Due to the controlled growth of crystalline MOFs in specific directions and the improvement of structural stability, terephthalic acid is currently the most promising bridging component. Benzoic acid (BA) has a single carboxyl linker, which has one less carboxyl group than terephthalic acid to coordinate with metal ions, resulting in unsaturated coordination of metal ions, making the synthesized MOF have abundant unsaturated active sites, thereby improving the oxygen evolution reaction (OER) and increasing electrochemical activity. At present, there are very few methods to enhance the electrochemical performance of bimetallic MOFs by using binary ligands. Summary of the invention

[0006] In view of the shortcomings of the prior art described above, the object of the present invention is to provide a benzoic acid-doped nickel / cobalt bimetallic MOF-based aqueous battery positive electrode material and a preparation method and application thereof. The method is simple to operate, has no special requirements for equipment, and is time-saving.

[0007] To achieve the above-mentioned object and other related objects, the present invention provides a method for preparing a benzoic acid-doped nickel / cobalt bimetallic MOF-based aqueous battery positive electrode material, wherein a porous carrier is immersed in a reaction solution for a solvothermal reaction to prepare a benzoic acid-doped nickel / cobalt bimetallic MOF-based positive electrode material; the reaction solution includes at least Ni 2+ 、Co 2+ and ligands comprising terephthalic acid and benzoic acid.

[0008] The present invention directly dopes the ligand by a one-step hydrothermal method. Compared with other low-temperature solvent exchange, multiple hydrothermal doping, etc., the operation is simpler and the time consumption is shorter, which provides a useful reference for the synthesis method of binary ligand doped bimetallic MOF. The method successfully improves the problems of low original capacity, low energy density, poor cycle stability of nickel-based MOF. The introduction of benzoic acid successfully improves the capacity of MOF, which is much higher than most of the nickel-based MOFs reported so far. The MOF synthesized in this application can play the corresponding advantages, and the large-scale production, the self-supporting electrode also avoids the use of conductive agents, binders, etc., is environmentally friendly, and has good application prospects in the fields of environment, energy, hybrid devices, etc.

[0009] The binary ligand system is prepared by simple solvent-assisted ligand doping. During the synthesis process, benzoic acid in the solution partially replaces terephthalic acid to ligand with metal ions, resulting in ligand deficiency in the MOF structure and affecting the overall coordination environment. Changes in the local coordination structure will not only produce a large number of charge-carrying defects, but also cause structural distortion to optimize the path of electron transfer in the crystal structure, regulate the electronic structure, and improve the conductivity, thereby affecting the electrochemical properties and catalytic activity of the material.

[0010] Preferably, Ni in the reaction solution 2+ Introduced via soluble nickel salts, such as nickel chloride.

[0011] Preferably, the reaction solution contains Co 2+ It is introduced via a soluble cobalt salt, such as cobalt chloride.

[0012] Preferably, in the reaction solution, Ni 2+ and Co 2+ The ratio of the sum of the amount of substance of the ligand to the amount of substance of the ligand is 1:1.

[0013] Preferably, in the reaction solution, the molar ratio of terephthalic acid to benzoic acid is 1:(0.05-0.40).

[0014] Preferably, in the reaction solution, Ni 2+ With Co 2+ The molar ratio of substances is (0.5~4):1.

[0015] Preferably, the temperature of the solvent thermal reaction is 100-180° C. and the time is 6-12 h.

[0016] Preferably, the reaction solution further comprises a solvent, and the solvent is a mixed solvent of DMF, ethanol and water.

[0017] Preferably, the porous carrier is nickel foam.

[0018] Preferably, before the solvothermal reaction, a pretreatment process of the porous carrier is also included, and the pretreatment process includes ultrasonically washing the porous carrier with hydrochloric acid, acetone, ethanol and water in sequence.

[0019] The present invention also provides a benzoic acid-doped nickel / cobalt bimetallic MOF-based aqueous battery positive electrode material prepared by the above preparation method.

[0020] The present invention also provides an application of the above-mentioned benzoic acid-doped nickel / cobalt bimetallic MOF-based aqueous battery positive electrode material in the energy field.

[0021] As described above, the present invention has the following beneficial effects: (1) Through the synergistic effect of benzoic acid and cobalt doping, the electronic structure of the Ni active site is optimized, and the oxidation state of the Ni active site is increased, so that the electrocatalytic activity of the prepared benzoic acid-doped nickel / cobalt bimetallic MOF-based cathode material is greatly enhanced; at the same time, the regulation of the two changes the morphology of the MOF material, exposing more active sites and improving the electrochemical performance of the MOF material. The electrode capacity is 1 mA cm -2 The current density reached 442.96 mAh g -1 ; at 30 mA cm -2 At this current density, the capacity can still reach 229.44 mAh g -1 , showing excellent rate performance (2) The benzoic acid-doped nickel / cobalt bimetallic MOF-based aqueous battery cathode material prepared by the present invention improves the OER performance of nickel-based MOF, with an OER overpotential of 284 mV and can be stable for 22 h under alkaline conditions, with a current retention rate of nearly 100%; (3) The benzoic acid-doped nickel / cobalt bimetallic MOF-based aqueous battery positive electrode material prepared in the present invention can be used as a new type of electrode material in energy applications, and also has broad application prospects in the fields of catalysis, energy storage, adsorption, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Shown are scanning electron microscope images of the products obtained in Example 1 (d) and Comparative Examples 1-3 (a-c).

[0023] Figure 2 Shown are the X-ray diffraction spectra of the products obtained in Example 1 and Comparative Examples 1 and 2.

[0024] Figure 3 Shown are Ni 2p X-ray photoelectron spectra of the products obtained in Example 1 and Comparative Examples 1 and 2.

[0025] Figure 4 Shown are the Co 2p X-ray photoelectron spectra of the products obtained in Example 1 and Comparative Example 3.

[0026] Figure 5 Shown are the O 1s X-ray photoelectron spectra of the products obtained in Example 1 and Comparative Examples 1 and 2.

[0027] Figure 6 Shown are linear voltammetric curves of the products obtained in Example 1 and Comparative Examples 1-3 in 1 M KOH electrolyte.

[0028] Figure 7 Shown is a graph showing the stability test results of the product obtained in Example 1.

[0029] Figure 8Shown are cyclic voltammetry curves of the products obtained in Example 1 and Comparative Examples 1-3 in 1 M KOH electrolyte.

[0030] Fig. 9 Shown are constant current charge and discharge curves of the products obtained in Example 1 and Comparative Examples 1-3 in 1 M KOH electrolyte.

[0031] Fig.10 Shown is the rate diagram of the product obtained in Example 1 in 1 M KOH electrolyte. DETAILED DESCRIPTION

[0032] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0033] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.

[0034] In addition, it should be understood that one or more method steps mentioned in the present invention do not exclude the existence of other method steps before or after the combination step or the insertion of other method steps between these explicitly mentioned steps, unless otherwise specified; it should also be understood that the combination connection relationship between one or more devices / apparatuses mentioned in the present invention does not exclude the existence of other devices / apparatuses before or after the combination device / apparatus or the insertion of other devices / apparatuses between these explicitly mentioned two devices / apparatuses, unless otherwise specified. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.

[0035] Example 1 The present application embodiment provides a method for preparing a benzoic acid-doped nickel / cobalt bimetallic MOF-based aqueous battery positive electrode material, comprising: (1) Washing of nickel foam: Cut a nickel foam of 3 cm*3 cm in size, and use 1 mol / L hydrochloric acid solution, acetone, ethanol and deionized water as cleaning agents for ultrasonic cleaning. The cleaning time of each cleaning agent is 10 min. Finally, put the cleaned nickel foam into a vacuum oven at 60°C for vacuum drying for subsequent use. (2) Add 30 mL of DMF, 4 mL of ethanol, and 4 mL of water to a 100 mL beaker, then add 0.35 mmol of nickel chloride hexahydrate, 0.35 mmol of cobalt chloride hexahydrate, 0.675 mmol of terephthalic acid, and 0.075 mmol of benzoic acid, and stir to completely dissolve to obtain a purple clear solution. Pour the mixed solution into a 100 mL reactor, and put the cleaned nickel foam in, and keep it at 140 ° C for 9 h. Take out the nickel foam and wash it repeatedly with DMF and ethanol. After the obtained product is vacuum dried at 60 ° C for 12 h, NiCoMOF-BA0.1-1 is finally obtained, represented by NCM BA -1, with a loading of approximately 1.6 to 2 mg cm -2 .

[0036] Example 2 The difference between Example 2 and Example 1 is that Ni 2+ With Co 2+ The molar ratio of substances is different, specifically 1.5:1, and the other process conditions are exactly the same.

[0037] In step (2), the amount of nickel chloride hexahydrate added is 0.45 mmol, the amount of cobalt chloride hexahydrate added is 0.3 mmol, and the total amount of nickel chloride hexahydrate and cobalt chloride hexahydrate added is controlled to be 0.75 mmol. The sample is represented by NCM BA -1.5, the loading capacity is about 1.6~2 mg cm -2 .

[0038] Example 3 The difference between Example 3 and Example 1 is that Ni 2+ With Co 2+ The molar ratio of substances is different, specifically 0.5:1, and the other process conditions are exactly the same.

[0039] In step (2), the amount of nickel chloride hexahydrate added is 0.2 mmol, the amount of cobalt chloride hexahydrate added is 0.5 mmol, and the total amount of nickel chloride hexahydrate and cobalt chloride hexahydrate added is controlled to be 0.75 mmol. The sample is represented by NCM BA -0.5, the loading capacity is about 2~4 mg cm -2 .

[0040] Example 4 The difference between Example 4 and Example 1 is that the molar ratio of terephthalic acid and benzoic acid is different, specifically 1:0.05, and the other process conditions are exactly the same.

[0041] The amount of terephthalic acid added was 0.7125 mmol, the amount of benzoic acid added was 0.0375 mmol, and the sample was expressed as NM BA0.05 , the loading amount is between 1.5 and 2 mg cm -2 .

[0042] Example 5 The difference between Example 5 and Example 1 is that the molar ratio of terephthalic acid to benzoic acid is different, specifically 1:0.025, and the other process conditions are exactly the same.

[0043] The amount of terephthalic acid added was 0.6 mmol, the amount of benzoic acid added was 0.15 mmol, and the sample was expressed as NM BA0.2 , with a loading of 2–4 mg cm -2 .

[0044] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that no Co is added to the reaction solution. 2+ , the ligand did not contain benzoic acid, and the rest of the process conditions were exactly the same.

[0045] In a 100 mL beaker, 30 mL DMF, 4 mL ethanol, and 4 mL water were added in sequence, and then 0.75 mmol nickel chloride hexahydrate and 0.75 mmol terephthalic acid were added and stirred to completely dissolve to obtain a green clear solution. The mixed solution was poured into a 100 mL reactor, and the cleaned nickel foam was put in and kept at 140 ° C for 9 h. The nickel foam was taken out and washed repeatedly with DMF and ethanol. The obtained product was vacuum dried at 60 ° C for 12 h to finally obtain NiMOF, represented by NM, with a loading of about 3~4 mg cm -2 .

[0046] Comparative Example 2 The difference between Comparative Example 2 and Comparative Example 1 is that the ligand further contains benzoic acid, specifically 0.675 mmol of terephthalic acid and 0.075 mmol of benzoic acid are added, and the other process conditions are exactly the same. Samples are represented by NM BA0.1 , the loading amount is between 1.5 and 2 mg cm -2 .

[0047] Comparative Example 3 The difference between Comparative Example 3 and Comparative Example 1 is that Ni 2+ Replaced by Co 2+ , the ligand also contains benzoic acid, specifically 0.75 mmol of cobalt chloride hexahydrate, 0.675 mmol of terephthalic acid and 0.075 mmol of benzoic acid were added, and the other process conditions were exactly the same. The sample is denoted as CM BA0.1, the loading amount is 3~4mg cm -2 .

[0048] The morphology of the materials obtained in Example 1 and Comparative Examples 1, 2, and 3 was characterized. Figure 1 As shown, Figure 1 (a), (b) and (c) are microscopic images of the materials of Comparative Examples 1-3, respectively. It can be seen that the morphologies of Comparative Examples 1 and 2 are both mesh nanosheets, and they grow vertically on nickel foam, indicating that the introduction of benzoic acid BA does not change the basic morphology, but it can be clearly seen that the thickness of the sample sheet becomes thinner, and the morphology of Comparative Example 3 is a quadrangular prism. Figure 1 (c) is a microscopic picture of the material of Example 1, and the microscopic morphology has changed and is in the form of flakes.

[0049] Figure 2 (a) shows the XRD spectra of the samples prepared in Example 1 and Comparative Examples 1 and 2. The diffraction peaks of Comparative Example 1 match well with those of nickel hydroxide terephthalate hydrate (PDF#638866), and the peaks are very sharp, indicating that Comparative Example 1 has an ideal crystal structure. The diffraction peaks of Comparative Example 2 are basically the same as those of Comparative Example 1. At the same time, the X-ray diffraction spectrum of Example 1 is also consistent with that of Comparative Example 1, indicating that the doping of Co does not change the crystal form of MOF. However, from Figure 2 As can be seen in (b), the introduction of benzoic acid and cobalt caused the 8-9° peak to shift to the right, where the partial replacement of terephthalic acid by benzoic acid caused partial atomic loss, and the replacement of nickel by cobalt broke the regular arrangement of metal ions. The addition of both produced lattice distortion and caused the peak to shift.

[0050] Figure 3 The Ni 2p X-ray photoelectron spectra of the products obtained in Example 1 and Comparative Examples 1 and 2 of the present invention are shown in Figure 2. Compared with Comparative Example 1, the Ni 2p 3 / 2 The binding energy of the Ni 2p in Example 1 increased by 0.13 eV. This result indicates that benzoic acid causes the loss of the linker in the MOF, which in turn changes the coordination environment of the active metal center. 3 / 2 Compared with Comparative Example 2, it is increased by 0.15 eV and moves to a higher binding energy. This may be due to the transfer of some electrons from Ni to Co through the oxygen of the ligand, thereby optimizing the electronic structure of the Ni active site, which is beneficial to improving the catalytic activity and electrochemical performance.

[0051] Figure 4 The Co 2p X-ray photoelectron spectra of the products obtained in Example 1 and Comparative Example 3 of the present invention are shown in Table 1. Compared with Comparative Example 3 (781.2 eV), the Co 2p in Example 1 is 3 / 2(781.4 eV) moves to a higher potential, indicating that the addition of Ni also affects the active sites of Co. Figure 5 The O 1s X-ray photoelectron spectra of the products obtained in Example 1 and Comparative Examples 1 and 2 of the present invention show that the binding energy of O 1s in Example 1 and Comparative Example 2 is increased by 0.1 eV compared with Comparative Example 1, indicating that both Example 1 and Comparative Example 2 have oxygen-related ligand defects, further confirming the doping of BA.

[0052] The benzoic acid-doped nickel / cobalt bimetallic MOF-based aqueous battery positive electrode material prepared in Example 1 of the present invention has both OER reaction activity and can be used as a catalyst, and has electrochemical activity and can be used as a positive electrode material for aqueous batteries.

[0053] Application Example 1 The products prepared in Example 1 and Comparative Examples 1-3 were used as working electrodes, saturated calomel electrode (SCE) was used as reference electrode and Pt foil was used as counter electrode in 1 M KOH, and their OER activity and stability were evaluated by linear voltammetric curves and voltage-time response tests in a three-electrode system.

[0054] Figure 6 The scan rate is 5 mV s -1 The linear voltammetric curves of Example 1 and Comparative Examples 1, 2, and 3 in 1 M KOH solution are shown in the following figure. It can be seen from the curves that when the current density is 10 mA cm -2 When the potential of Example 1 (1.514 V) is significantly lower than that of Comparative Example 1 (1.563 V) and Comparative Example 2 (1.543 V), and also lower than that of Comparative Example 3 (1.519 V). This shows that all of the above materials have OER catalytic performance, but the catalytic activity of Example 1 is higher. This is because the doping of benzoic acid causes NiMOF to lack some connectors, which changes its coordination environment, improves the oxidation state of Ni active sites, and improves its catalytic activity. At the same time, the introduction of Co further improves the OER performance of MOF. The doping of benzoic acid and the doping of Co have a synergistic effect, which together make Example 1 have higher OER catalytic activity.

[0055] Figure 7 This is a current-time curve of the product obtained in Example 1 of the present invention in 1 M KOH solution. The results show that the material can be continuously tested for 22 h, and it is found that the current is basically maintained at 100%, indicating that the material has good OER stability.

[0056] Application Example 2 The electrochemical performance of the products prepared in Example 1 and Comparative Examples 1, 2 and 3 was tested in a three-electrode system using a saturated calomel electrode (SCE) as a reference electrode and a Pt foil as a counter electrode in 1 M KOH. Figure 8 The scan rate is 5 mV s -1 In the cyclic voltammetry (CV) curves under 400 nm, a pair of redox peaks were observed at 0.1–0.5 V (vs. SCE), corresponding to the oxidation of NiMOF and OH. - The redox reaction of ions. According to the CV graph, it can be found that the addition of BA increases the capacity of the material, and the doping of Co causes the Ni redox peak to shift to a lower potential.

[0057] Fig. 9 The constant current charge-discharge curves of Example 1 and Comparative Examples 1, 2, and 3 are shown. The curves show the same results as the CV curves. The electrode material prepared in Example 1 has a charge-discharge rate of 1 mA cm -2 The capacity at the current density is 442.96 mAh g -1 Much higher than the other comparison samples.

[0058] Fig.10 The charge-discharge curves of Example 1 at different current densities show that at 30 mA cm -2 At a high current density of , the capacity of the electrode material prepared in Example 1 still reaches 229.44 mAh g -1 , showing excellent rate performance.

[0059] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for preparing a benzoic acid-doped nickel / cobalt bimetallic MOF-based aqueous battery positive electrode material, characterized in that: The porous carrier is immersed in the reaction solution for solvent thermal reaction to obtain benzoic acid doped nickel / cobalt bimetallic MOF-based positive electrode material; the reaction solution includes at least Ni 2+ 、Co 2+ and ligands comprising terephthalic acid and benzoic acid.

2. The preparation method according to claim 1, characterized in that: In the reaction solution, Ni 2+ and Co 2+ The ratio of the sum of the amount of substance of the ligand to the amount of substance of the ligand is 1:

1.

3. The preparation method according to claim 2, characterized in that: In the reaction solution, the molar ratio of terephthalic acid to benzoic acid is 1:(0.05-0.40).

4. The preparation method according to claim 2, characterized in that: In the reaction solution, Ni 2+ With Co 2+ The molar ratio of substances is (0.5~4):

1.

5. The preparation method according to claim 1, characterized in that: The temperature of the solvent thermal reaction is 100~180℃ and the time is 6~12h.

6. The preparation method according to claim 1, characterized in that: The reaction solution also includes a solvent, which is a mixed solvent of DMF, ethanol and water.

7. The preparation method according to claim 1, characterized in that: The porous carrier is nickel foam.

8. The preparation method according to claim 1, characterized in that: Before the solvent thermal reaction, a pretreatment process of the porous carrier is also included, and the pretreatment process includes ultrasonically washing the porous carrier with hydrochloric acid, acetone, ethanol and water in sequence.

9. A benzoic acid-doped nickel / cobalt bimetallic MOF-based aqueous battery positive electrode material prepared by the preparation method according to any one of claims 1 to 8.

10. Application of the benzoic acid-doped nickel / cobalt bimetallic MOF-based aqueous battery positive electrode material as claimed in claim 9 in the energy field.

Citation Information

Patent Citations

  • Metal organic skeleton electrode material of supercapacitor and preparation method of the electrode material

    CN105977040A

  • Morphological control method of metal oxide / carbon negative electrode material for lithium ion battery

    CN106784658A

  • Bimetal MOFs electrocatalyst as well as preparation method and application thereof

    CN117661012A

  • Lithium-rich manganese-based positive electrode material and preparation method and application thereof

    CN117996027A

  • Metal-organic framework filter and preparation method thereof

    US20180257041A1